PERAN KELOMPOK TANI SAYURAN ORGANIK TERHADAP PENGEMBANGAN EKONOMI LOKAL (Studi Kasus Desa Batur, Kabupaten Semarang) - Indra Permana; Darwanto . (Jurnal Bisnis dan Ekonomi, 2016)
Healthy lifestyle which was impleted by the Indonesian people, pushing up demand for organic vegetables products. Cultivation of oganic vegetables can be classified as local potential as serve as a source of economic local. The role of organic vegetables farmer groups in the local economic development is needed as a place to learn, solution of the problems cropping and product marketing media. The transition farming systems and farmer’s understanding of organic vegetables become a major problem in the cultivation of organic farming. The purpose of this research is identify the role of the farmer organic vegetables is an effort to local economic development and the strategy of local economic development through the role of farmer groups. This study use qualitative methods. The result of this research showed in the cultivation of organic vegetables requires the role of farmer groups in each stage of production and marketing of products. The farmer groups provide problems solution the cultivation of organic vegetables at each regular meeting between members of farmer groups. The farmers who did not join the farmer groups will have difficulty in marketing the product and the selling price of organic vegetables is unstable. The existence of farmer institutions will make it easier for governments and other stakeholders to facilitate and provide reinforcement to the farmers. Keywords : local economic development, institutions, social capital